Application of environmentally-friendly and energy-saving materials in building decoration - Chen Li sheng; Ding Yudi; Chen Lei (E3S Web of Conferences, 2021)
With the rapid development of urban construction, the state and society gradually realize the significance of environmental protection and put forward higher requirements for the specific construction of the building industry. In this paper, it summarizes and sorts out the environmentally-friendly and energy-saving materials through analyzing and comparing common building materials on the market. During building decoration, make full use of energy-saving and environmentally-friendly building materials to promote their wide application in the construction industry.